Communicating COVID-19 pandemic : media coverage of the headquarters and the use of persuasion strategies in Croatia - Grbeša Zenzerović, Marijana (Array, 2020)
In February 2020 Croatia was affected by the COVID-19 global pandemic. A challenging task of communicating the pandemic was assumed by the people associated with the Headquarters of Civil Protection of the Republic of Croatia. The goal of this study was to examine how three of them were covered in the media and to test if and how they were using pandemic-related strategies of persuasion to achieve public compliance. The findings indicate that the coverage of the key communicators during the first three months of the pandemic was overwhelmingly positive. Moreover, in the early stages of the pandemic none of the examined news sites was really pushing issues or angles that questioned pandemic-related policies or actions of the Headquarters. Examination of the rhetoric of the key coronavirus communicators has established that they have embraced persuasive strategies that are typical of pandemic communication, most notably the use of fear appeals, military metaphors and insistence on messages of 'togetherness' and conversely, 'pandemic shaming'. The article concludes that professional credibility and favorable media representation of Croatian coronavirus envoys, along with adopted persuasive strategies, have probably encouraged people to trust their decisions and comply with restrictive measures that have suspended their freedoms and changed their life routines almost overnight.